Design, synthesis, molecular modeling, and biological evaluation of acrylamide derivatives as potent inhibitors of human dihydroorotate dehydrogenase for the treatment of rheumatoid arthritis - Fanxun Zeng; Shiliang Li; Guantian Yang; Yating Luo; Tiantian Qi; Yingfan Liang; Tingyuan Yang; Letian Zhang; Rui Wang; Lili Zhu; Honglin Li; Xiaoyong Xu (Elsevier, 2021)
Human dihydroorotate dehydrogenase (DHODH) is a viable target for the development of therapeutics to treat cancer and immunological diseases, such as rheumatoid arthritis (RA), psoriasis and multiple sclerosis (MS). Herein, a series of acrylamide-based novel DHODH inhibitors as potential RA treatment agents were designed and synthesized. 2-Acrylamidobenzoic acid analog 11 was identified as the lead compound for structure-activity relationship (SAR) studies. The replacement of the phenyl group with naphthyl moieties improved inhibitory activity significantly to double-digit nanomolar range. Further structure optimization revealed that an acrylamide with small hydrophobic groups (Me, Cl or Br) at the 2-position was preferred. Moreover, adding a fluoro atom at the 5-position of the benzoic acid enhanced the potency. The optimization efforts led to potent compounds 42 and 53‒55 with IC50 values of 41, 44, 32, and 42 nmol/L, respectively. The most potent compound 54 also displayed favorable pharmacokinetic (PK) profiles and encouraging in vivo anti-arthritic effects in a dose-dependent manner.